Biometric Based on Fingerprint - Suri, Samiksha (International Journal of Computer Sciences and Engineering, 2025)
Security has always been a major concern for authentication over networking. Fingerprints are one of the biometrics which plays an important role in identifying a person based on some minutiae features. This is one of the most commonly used algorithms for extracting features that characterizes a fingerprint. This biometrics has several applications like e-governance, commercial and forensic. The fingerprint biometric offers a higher degree of security and personal privacy. Emerging privacy concerns with the database acquisition and lack of availability of large scale fingerprint databases have posed challenges in exploring this technology for large scale applications. Fingerprint recognition looks for the unique patterns of ridges and valleys that are present in an individual’s fingerprint. These patterns are unique to every individual and thus help to identify individuals from an entire population. Verification and identification are the two ways in which an individual’s identity can be determined using biometric technology. This research also developed user-friendly software to synthesize fingerprint databases, which could help to advance further research in fingerprint biometrics.